1976
DOI: 10.1111/j.1600-0722.1976.tb00483.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chlorhexidine mouthrinse on healing after gingivectomy

Abstract: – The purpose of this investigation was to evaluate the effect of 0.2 % chlorhexidine gluconate mouthrinse following gingivectomy on plaque under the dressing and on healing. Twenty‐eight patients with indications for gingivectomy were selected. Coe‐Pak® was used as surgical dressing. In addition to usual home care, the patients rinsed twice daily with chlorhexidine or placebo for 21 d after surgery. The study followed a cross‐over, double‐blind design. Gingival exudate was assessed and P1 I and G I were regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
5

Year Published

1978
1978
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 8 publications
0
28
0
5
Order By: Relevance
“…For example, when used as a chemical toothbrush after oral/periodontal surgery or implant placement, when mechanical cleaning of the wound is not indicated, healing was even promoted when chlorhexidine was used. Signs of inflammation decreased and a reduction in microbial contamination of the wound compared with the control was shown . Sanchez et al.…”
Section: Additional Use Of Antibacterial Mouthrinsesmentioning
confidence: 96%
“…For example, when used as a chemical toothbrush after oral/periodontal surgery or implant placement, when mechanical cleaning of the wound is not indicated, healing was even promoted when chlorhexidine was used. Signs of inflammation decreased and a reduction in microbial contamination of the wound compared with the control was shown . Sanchez et al.…”
Section: Additional Use Of Antibacterial Mouthrinsesmentioning
confidence: 96%
“…In contrast to that, the clinical use of CHX after oral surgical interventions, tooth extractions or implant placement showed significantly less signs of inflammation and improvement of gingival health by reduction of the microbial contamination of the wound [19][20][21]. A further disadvantage is given by the inactivation of CHX by binding on blood, serum proteins and sulcus fluid which was shown in in vitro studies [22,23].…”
Section: Introductionmentioning
confidence: 93%
“…Also, the start of mechanical and chemical plaque control on day 3 after the surgical intervention was considered early enough to interfere with the maturation of existing biofilms (Lang et al 1973). Earlier studies on the application of CHX containing dressings (Asboe‐Jørgensen et al 1974, Hamp et al 1975, Plüss et al 1975, Langebaek & Bay 1976) or rinses with CHX during a post‐surgical healing period of 2 months (Westfelt et al 1983a) have demonstrated the beneficial effects of CHX in a post‐surgical care protocol. Also, control of patient oral hygiene as measured by FMPSs and FMBSs were shown by Tonetti et al (1996) to have a significant effect on success and complication rates of periodontal regenerative surgery.…”
Section: Discussionmentioning
confidence: 99%
“…For all oral rinsing products with anti‐microbial and anti‐plaque properties, CHX has long been considered as the gold standard (Lang & Brecx 1986, Jones 1997). Hence, its application following periodontal surgical procedures should promote the healing process, reduce post‐surgical complications, as well as improve clinical parameters (Asboe‐Jørgensen et al 1974, Hamp et al 1975, Plüss et al 1975, Langebaek & Bay 1976, Westfelt et al 1983a).…”
mentioning
confidence: 99%